Minorias sociais e seus obstáculos à representação no legislativo brasileiro - Castro, Leonardo Aires de (Universidade Federal de São Carlos, 2018)
This work aims to analyze the obstacles to access to political representation of Brazilian social minorities in the House of Representatives. By social minorities, it is understood historically subordinated groups that present compared to other social segments notorious social and representative inequality, namely: women, nonwhites and lower social classes. The focus of the analysis are the 2014 elections and unsatisfactory acquisition according to the logic of descriptive representation of seats in the House of Representatives and 2010 and 2006 Legislatures as the elect and their votes on matters concerning the correction of inequality factors of representative. The project asks if historical conditions of inequality about economic, racial and gender in Brazilian society explain the maintaining status quo with regard to access to social representation of minorities in the House of Representatives. We start from the hypothesis that historical-structural conditions of inequality of these groups hinder representative access because affect negatively on the electoral competition of these actors. Beside these conditions, oligarchies represented in the legislative act to maintain this process of exclusion, in the dealings of subjects that aim to correct or improve institutional mechanisms.
Social minorities and their obstacles to representation in the Brazilian Legislative
Keywords: Representação descritiva; Minorias sociais; Acesso representativo; Descriptive representation; Social minorities; Representative access; CIENCIAS HUMANAS::CIENCIA POLITICA::COMPORTAMENTO POLITICO